(3ebOeI aj fXe GdeYdheGJ GdEOGQjI (BMIS /s - (3GdTQeGf, RjGO eMeOs ((3YeGf(B: s (3OGQ UaGA ddfTQ hGdJhRjY(B, s, 2004)
(3GdeYdheGJ GdEOGQjI(B- (3GdfXGe(B- (3eQGMd JWhQ fXe GdeYdheGJ GdEOGQjI(B- (3caGAI fXe GdeYdheGJ HGSJNOGe HjQJ(B- (3fXe GdeYdheGJ GdEOGQjI(B.s
(3GdedGMb U(B. 359 (3GdeQGLY U(B. 361s
Keywords: (3GdEOGQIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s